The Influence Of Brand Ambassador And Sales Promotion On Online Repurchase Intention (Case Study On Tokopedia E-Commerce) - Singgih, Mohamad; Agustin Rachmaningrum, Ratih; Pantja Putra, Suatmo; Wunga, Febriani (Publisher Cv. Inara, 2024)
The use of brand ambassadors and sales promotions in online shopping applications also has an influence on repeat purchase interest. This becomes interesting to study in the E-Commerce era. The aim of the research is to analyze the influence of brand ambassadors and sales promotions on online repurchase intention. Research respondents are customers who have made purchases through the Tokopedia e-commerce application. This research uses a sample of 100 respondents using data collection techniques through questionnaires. The analysis technique uses multiple linear regression analysis with the SPSS program. Based on the results of the analysis, it shows that the brand ambassador and Sales Promotion variables positive influenced and significant on the online repurchase intention variable of e-commerce application users. The research findings also show that the sales promotion variable has a dominant influence on online repurchase intention variable.